Public employee’s dignity and the new public administration’s digital and robotic model (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper highlights the theme of legal protection reserved to human dignity in public employment, according to the global spread of digital era, including the A.I. development in decision making process of the public administration. The target is remarking attention on the risks probably occuring to consider the implementation of A.I. in connection with the reduction of human apport to set public functions and services, despite the development of roboethics principles and first legal rules, that seems not yet able to generate a clear order, also referring to the aim to preserve human nature at the base of law principles.
Keywords: Public employee; dignity; A.I.; public administration model; digital era